La Finance durable et l’ISR au service d’une économie pérenne et responsable : Quelle dynamique au MAROC ? - Meryem Chiadmi (European Scientific Journal, ESJ, 2017)
This paper focuses on sustainable finance and its most dominant form, socially responsible investment (SRI). Favored by the emergence of sustainable development, SRI consists in integrating into the investment decision process the respect of extra-financial criteria and reflects a developed practice of corporate social responsibility (CSR). The implementation of investment strategies based on sustainable financing approaches has increased in recent years. Our objective is to highlight the situation of this form of sustainable finance in Morocco and to answer the following question: "Morocco which has inscribed its investment strategies and its growth policy in logic of sustainable development that it put in place to attract investors (companies or savers) concerned societal and environmental issues?" The study of the Moroccan context, with emphasis on the commitment of the different actors, allowed us to draw up an inventory of the dynamics of this finance and to conclude that Morocco has a head start in its region and is moving more and more towards green financing but we are still far from the development rates achieved in the world. Its SRI market is still embryonic and represents a niche to exploit. Obstacles still hinder the transition to a sustainable and responsible economy and it is appropriate for all actors (State, private or public institutions, civil society and individuals) to deploy even more efforts to meet the requirements of a changing world.